2018
DOI: 10.22270/ujpr.v3i2.133
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Leptospirosis Amongst Slaughterhouse Workers and Butchers in Sana'a City-Yemen

Abstract: Zoonotic infections can be work-related risks to people who labor in nearby connection with animals. The goals of present study were to find out the prevalence of leptospira antibodies and impact factors of leptospirosis among this risk groups in Sana'a city. A 267 serum samples were assembled from the study groups and a written record was completed for all workers to record individual and behavioral information. The sera were tested for leptospirosis IgG antibodies by commercial ELISA technique. The acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Among studies from the United Arab Emirates, one showed a seroprevalence of 4.1% [ 58 ] in camels, and another showed a seroprevalence of 1.7% in cattle [ 59 ]. In Yemen, a seroprevalence of 41.3% [ 60 ] and 42% [ 61 ] by ELISA was reported in humans, and a seroprevalence of 6.7% by SSI was reported in camels in Saudi Arabia [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among studies from the United Arab Emirates, one showed a seroprevalence of 4.1% [ 58 ] in camels, and another showed a seroprevalence of 1.7% in cattle [ 59 ]. In Yemen, a seroprevalence of 41.3% [ 60 ] and 42% [ 61 ] by ELISA was reported in humans, and a seroprevalence of 6.7% by SSI was reported in camels in Saudi Arabia [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, when the same type of group was chosen, low seroprevalence variability was observed. For instance, in the case of humans in Yemen, when only two publications targeting similar types of groups (people at risk) were reported, the seroprevalence ranged between 41.3% [ 60 ] and 42% [ 61 ]. The sampling period may also have had a major impact on the incidence of leptospirosis throughout the year because of the seasonal pattern of the disease and its recrudescence in specific seasons, in which the highest incidence occurs mainly in summer or/and fall in temperate countries and in rainy seasons in warm-climate regions [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Hadhramout, Yemen, there are limited data on neglected tropical diseases (which are highly associated with war, poverty, and deteriorating health systems). Although recent studies have discussed trachoma, tuberculosis, leptospirosis, and brucellosis [1][2][3][4][5][6][7][8][9][10][11] , but VL studies have been very old or limited and did not involved Hadhramout areas 12 . VL, is a protozoa disease caused by Leishmania species that is fatal if not treated.…”
Section: Introductionmentioning
confidence: 99%
“…Yemen is one of the developing countries where infectious microorganisms are the main causes of human suffering including tuberculosis, limited research has been conducted in investigating infectious diseases such as viral hepatitis 1-7 , parasitic infections 8,9 , leptospirosis 10 , trachoma 11 , tuberculosis 12 , fungal infections 13 . Tuberculosis is one of the serious public health problems in Yemen 12 , as tuberculosis is one of the main causes of death, although it is a curable infectious disease, as well as a major cause of morbidity in developing countries such as Yemen 14 .…”
Section: Introductionmentioning
confidence: 99%